2021
DOI: 10.1111/aas.13973
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphataemia is common in patients with aneurysmal subarachnoid haemorrhage

Abstract: Introduction Hypophosphataemia is common in critically ill patients, but neither its prevalence nor its association with outcome have been investigated specifically in patients with aneurysmal subarachnoid haemorrhage (aSAH). Methods Patients with aSAH and at least one phosphate measurement were included from two independent cohorts; an American cohort extracted from two open‐access databases (Medical Information Mart for Intensive Care‐III and eICU Collaborative Research Database v. 2.0) and a Danish cohort c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Septic shock is characterized by profound circulatory, cellular, and metabolic abnormalities and is the leading cause of death in hospitals [1][2][3]20 . Numerous studies have revealed that abnormalities in serum phosphate levels are associated with worse outcomes in various diseases [21][22][23][24] . However, the relationship between serum phosphate levels and 28-day mortality in patients with septic shock remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Septic shock is characterized by profound circulatory, cellular, and metabolic abnormalities and is the leading cause of death in hospitals [1][2][3]20 . Numerous studies have revealed that abnormalities in serum phosphate levels are associated with worse outcomes in various diseases [21][22][23][24] . However, the relationship between serum phosphate levels and 28-day mortality in patients with septic shock remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate is dynamically changing in the body 8,15 . Several studies have identified that changes in serum phosphate levels are predictive factors for adverse outcomes in critically ill patients [21][22][23][24] . Dekker et al found that changes in serum phosphate levels during high-flux hemodialysis or hemodiafiltration are strongly related to the calcification propensity in dialysis patients 40 .…”
Section: Discussionmentioning
confidence: 99%